Dilute Acid Hydrolysis Of Oil Palm Empty Fruit Bunches, Rice Husks, Rice Straws And Oil Palm Trunks To Produce Glucose And Xylose - Cheng, Xin You (2013)
Lignocellulose biomass are potential renewable sources to produce biofuels that may replace the non-renewable fossil fuels. Oil palm empty fruit bunches (EFB), oil palm trunks (OPT), rice husks and rice straws were used to produce fermentable sugars via acid hydrolysis. Glucose enzymatic assay was tested and shown to be affected by the colour of the hydrolysate while High Performance Liquid Chromatography (HPLC) analysis was shown to be no problem with the colour of the hydrolysate in determining glucose and xylose concentrations. Four types of biomass chosen were hydrolyzed using a simple two-stage acid hydrolysis method to obtain fermentable sugars. Three hydrolysis parameters i.e. hydrolysis duration, hydrolyzing acid concentration and the concentrated acid to raw material weight ratio were studied and optimized for every biomass. The results were interpreted via the sugar yields of glucose and xylose by HPLC. The simple two-stage acid hydrolysis method was shown to achieve good total glucose and xylose yields. In the parameters optimization, the most suitable hydrolysis duration for all the four types of biomass used was 4 hours. As for the other two parameters, 4.5 % (v/v) was found to be the most suitable hydrolyzing acid concentration while the ratio of 4:1 (w/w) was found to be the most suitable concentrated acid to raw material weight ratio for all the four types of biomass. By using the simple two-stage acid hydrolysis and the optimized parameters, the total glucose and xylose yields achieved for EFB, OPT, rice husks and rice straws were 30.71 % (w/w), 29.41 % (w/w), 29.31 % (w/w) and 35.16 % (w/w) respectively.